1997
DOI: 10.1038/sj.jim.2900464
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production by Saccharomyces cerevisiae in biofilm reactors

Abstract: Biofilms are natural forms of cell immobilization in which microorganisms attach to solid supports. At ISU, we have developed plastic composite-supports (PCS) (agricultural material (soybean hulls or oat hulls), complex nutrients, and polypropylene) which stimulate biofilm formation and which supply nutrients to the attached microorganisms. Various PCS blends were initially evaluated in repeated-batch culture-tube fermentation with Saccharomyces cerevisiae (ATCC 24859) in low organic nitrogen medium. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…Novel engineered support materials are being developed to improve immobilized bioprocesses, such as a nutrient-containing "plastic composite support," which outperforms normal polypropylene supports in ethanol production (Demirci et al, 1997). Another new support constructed from metal mesh particles aims to reduce the high shear stress sometimes suffered by immobilized bacteria (Kargi and Toprak, 1994).…”
Section: Immobilizationmentioning
confidence: 99%
“…Novel engineered support materials are being developed to improve immobilized bioprocesses, such as a nutrient-containing "plastic composite support," which outperforms normal polypropylene supports in ethanol production (Demirci et al, 1997). Another new support constructed from metal mesh particles aims to reduce the high shear stress sometimes suffered by immobilized bacteria (Kargi and Toprak, 1994).…”
Section: Immobilizationmentioning
confidence: 99%
“…Fermentation was performed in a Chemostat Ommi Culture Plus (Virtis) with a volume of 2 L operation, adjusting stirring at 120 rpm and maintaining a temperature of 30°C. The medium equivalent to mango juice was similar to that described by Demirci et al [25] by adjusting the composition of the medium to a concentration of 200 g L −1…”
Section: Experimental Setup and Proceduresmentioning
confidence: 96%
“…Nevertheless, there was greater productivity, which indicates that it is possible to obtain high alcohol content with a lower requirement of substrate, but with the disadvantage of residual glucose in the medium; this problem can be solved with sequenced systems, as suggested by Demirci et al [25]. Another alternative of solving this problem is to increase the cell number or inoculum size within the reactor.…”
Section: Yeast -Industrial Applicationsmentioning
confidence: 99%
“…Plastic composite support (PCS) has been developed to provide an ideal surface for biofilm formation, which is an extrusion product of a mixture of polypropylene and nutritious compounds [28]. Many studies have shown that PCS biofilm reactors can enhance production of ethanol [13], organic acid [36], and bacterial cellulose [11]. Moreover, the slow release of the ingredients on PCS, such as carbon sources, nitrogen sources, and minerals, can persist for more than 1 year without affecting its efficiency when performing continuous fermentation [12,13,18].…”
Section: Introductionmentioning
confidence: 99%